Oxidation of waxes using microwave-generated singlet molecular oxygen - Beigley, John Robertson (Department of Chemistry, 2016)
Waxes are a widely used chemical commodity throughout the world due to certain intrinsic properties. Applications vary widely, including such obvious ones as candles and polishes, less obviously coatings, ink, and cosmetics, and more obscurely, hot melt adhesives, textile processing and chewing gum. The waxes used are obtained from a variety of sources, natural, mineral, and synthetic. The properties of the wax determine its suitability for a particular application. For certain of the latter, a wax containing Oxygen groups is often the most appropriate type. While there are a number of such waxes that occur naturally, there are also many more in which the raw wax has undergone oxidation by chemical processes. Generally, this is done utilising elevated temperatures, and passing air or oxygen through the wax. Oxidation then takes place via a free radical process. Singlet molecular oxygen is a higher-energy state species of oxygen, in which the two electrons in the π* 2p antibonding molecular orbitals, while remaining unpaired, are excited to antiparallel spin. Reactions of singlet oxygen are very site-speciﬁc, resulting in more speciﬁc products compared to the free radical process. It was considered that oxidation of waxes by reaction with singlet oxygen might produce different products compared to the thermal oxidation, and also compared to oxidation using ozone. An apparatus was set up to test this theory. The singlet oxygen was generated by passing a stream of oxygen through a microwave beam to form a plasma, the resulting singlet oxygen-containing gas being reacted with molten wax. Optimisation of the setup was performed before performing reactions, using several different waxes. The experiments were duplicated by ones with the microwave switched off, so that any results could be ascribed to the presence of singlet oxygen, and not normal oxygen. A similar apparatus was set up to react the same waxes with ozone, the latter being generated by passing oxygen through an electrical discharge-type generator. Blank runs with the electric discharge apparatus switched off, were also carried out to be able to distinguish any reaction due to the unozonised oxygen. The results showed that the singlet oxygen only reacted with a particular type of wax, namely oxidised polyethylene wax (AC6-29), although other effects were caused by the heat of the plasma. The ozone, on the other hand, reacted readily with all types of waxes tested. Other experiments were also conducted to investigate the use of microwave technology for chemical purposes, including development of an analytical method for saponification value determination in which microwaves replaced conventional heating.